2015
DOI: 10.3746/pnf.2015.20.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sorption and Thermodynamic Properties of Vacuum-Dried Capsosiphon fulvescens Powder

Abstract: ABSTRACT:The moisture sorption isotherms of vacuum-dried edible green alga (Capsosiphon fulvescens) powders were determined at 25, 35, and 45 o C and water activity (aw) in the range of 0.11∼0.94. An inversion effect of temperature was found at high water activity (>0.75). Various mathematical models were fitted to the experimental data, and Brunauer, Emmett, and Teller model was found to be the most suitable model describing the relationship between equilibrium moisture content and water activity (<0.45). Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
3
5
1
Order By: Relevance
“…According to Zuo et al. (2015), there is also a reduced number for sorption sites that actively bind water with increased temperature while water molecules movement increases resulting in reduced Mo values. The least Mo value obtained (8.00%) indicated that during dehydration, moisture content should not be allowed to go below 8% in order to prevent unnecessary energy and time consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zuo et al. (2015), there is also a reduced number for sorption sites that actively bind water with increased temperature while water molecules movement increases resulting in reduced Mo values. The least Mo value obtained (8.00%) indicated that during dehydration, moisture content should not be allowed to go below 8% in order to prevent unnecessary energy and time consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The monolayer moisture differences for dehydrated mango can be attributed to the different physical-chemical composition of the varieties used and the difference in choice of techniques of drying used. According toZuo et al (2015), there is also a reduced number for sorption sites that actively bind water with increased temperature while water molecules movement increases resulting in reduced Mo values. The least Mo value obtained (8.00%) indicated that during dehydration, moisture content should not be allowed to go below 8% in order to prevent unnecessary energy and time consumption.…”
mentioning
confidence: 99%
“…where a and b are constants. R 2 and P (%) were used to evaluate Equation (8) for goodness of fit (Zuo et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The CCE describes the a w of a food as a function of temperature for a given MC (Tadapaneni et al., 2017). This equation was initially developed to evaluate the impact of temperature on the a w of a pure system (Labuza & Altunakar, 2007), but has been used to model changes of a w in different dried food products or ingredients, including blueberry, pineapple, potato, and green algae, over a wide range of temperatures (Hossain et al., 2001; Lim et al., 1995; McMinn & Magee, 2003; Zuo et al., 2015). Recent studies show that by using the CCE, MSIs can be obtained for a larger range of temperatures and in less time than traditional methods (Jin et al., 2019; Tadapaneni et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were weighed periodically until constant weight is reached. The equilibrium moisture sorption (EMS) isotherms were determined by the gravimetric method according to the following equation [22].…”
Section: D)water Sorption Isotherm Measurementmentioning
confidence: 99%